Cyanoacrylate glue application in oral surgery: a mini-review - Król, Mateusz; Kolasińska, Julia; Maciaszczyk, Sławomir; Nijakowski, Kacper (Journal of Stomatology, 2025)
Cyanoacrylate adhesives have gained attention as a viable alternative to traditional sutures in oral surgery due to their biocompatibility, biodegradability, and bacteriostatic properties. This review evaluated the clinical ap-plications, advantages, and limitations of cyanoacrylate adhesives in dental surgical procedures. In analysis of 11 studies, the review explored their use in various contexts, including post-extraction socket dressing, impacted third molar extractions, alveoloplasty, management of oroantral communication, and free gingival grafts. Findings indicate that cyanoacrylates often provide reduced post-operative discomfort, improved hemostasis, and faster recovery in certain clinical settings compared with sutures. For instance, split-mouth studies have shown that patients experience statistically lower pain and reduced swelling when cyanoacrylates are used for wound closure. Additionally, histological studies highlight a lower inflammatory response and similar connective tissue formation in wounds treated with adhesives compared with sutures. Despite these advantages, certain limitations persist, such as requirement for a dry environment during application, sensitivity to large transverse forces, and risk of thermal cell damage due to the exothermic polymerization reaction. While cy-anoacrylates have demonstrated significant potential to simplify surgical techniques and enhance patient comfort, further research is necessary to develop standardized protocols and ensure safety. These adhesives should complement, rather than entirely replace, conventional sutures, with case-specific considerations guiding their use.